2020
DOI: 10.1155/2020/5257431
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Maternal Near-Miss and Its Determinants among Northwest Ethiopian Women: A Cross-Sectional Study

Abstract: Background. Life-threatening situations might arise unexpectedly during pregnancy. Maternal near-miss can be a proxy for maternal death and explained as women who nearly died due to obstetric-related complications. It is recognized as the predictor of level of care and maternal death. Maternal near-miss evaluates life-threatening pregnancy-related complications, and it directs the assessment of the quality of obstetric care. Objective. To determine the proportion and factors associated with maternal near-miss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Moreover, the study has revealed that the odds of developing maternal near-miss events among women with family income of less than 100 USD were 3.33 times more compared to those with more than 500 USD [OR = 3.333, 95%CI = (1.055-10.530)]. The result of this study was consistent with other study conducted in Ethiopia a year ago divulged that women with the lowest monthly income (1000 ETB) had 3.99 times the chance of having maternal near-miss than those with a monthly income more than or equal to 3001 ETB [30]. This is not surprising since over 99% of maternal deaths occur in low-and middle-income countries due to extreme poverty resulting in lack of access to quality healthcare and education of women [2].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the study has revealed that the odds of developing maternal near-miss events among women with family income of less than 100 USD were 3.33 times more compared to those with more than 500 USD [OR = 3.333, 95%CI = (1.055-10.530)]. The result of this study was consistent with other study conducted in Ethiopia a year ago divulged that women with the lowest monthly income (1000 ETB) had 3.99 times the chance of having maternal near-miss than those with a monthly income more than or equal to 3001 ETB [30]. This is not surprising since over 99% of maternal deaths occur in low-and middle-income countries due to extreme poverty resulting in lack of access to quality healthcare and education of women [2].…”
Section: Discussionsupporting
confidence: 89%
“…Based on women reports of their reason for experiencing delay in receiving care, staff workload 75 (47.2%), lengthy admission process 35 (22%), health professionals negligence 27 (17%), lack of supply or drugs 23 (14.5%), delay in providing informed consent 3 (1.9%) and unfunctional operating room 2(1.3%) were stated. These findings were also identified as a reason for maternal third delay in a cross-sectional study conducted in Brazil [ 30 ], University of Gondar Referral Hospital [ 31 ], Arsi Zone [ 26 ], and a multicountry study done in seven countries [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 However, the MNM ratio in this study was nearly 3.5 times higher than the MNM ratio of an 8.01 per 1000 live births described in a facility-based cross-sectional study conducted in the capital, Addis Ababa 26 and nearly two times higher than a similar study conducted in University of Gondar Referral Hospital, a similar setup in Northwest Ethiopia. 27 …”
Section: Discussionmentioning
confidence: 99%